2021
DOI: 10.21037/qims-20-525
|View full text |Cite
|
Sign up to set email alerts
|

Deep transfer learning based on magnetic resonance imaging can improve the diagnosis of lymph node metastasis in patients with rectal cancer

Abstract: Background: Lymph node (LN) metastasis is the main prognostic factor for local recurrence and overall survival of patients with rectal cancer. The accurate evaluation of LN status in rectal cancer patients is associated with improved treatment and prognosis. This study aimed to apply deep transfer learning to classify LN status in patients with rectal cancer to improve N staging accuracy. Methods:The study included 129 patients with 325 rectal cancer screenshots of LN T2-weighted (T2W) images from April 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Gattringer et al analyzed the effect of magnetic resonance diffusion imaging in central system diseases [ 9 ]. Li et al found that in acute cerebral infarction, a large number of water molecules enter the cells, resulting in intracellular edema and reduced diffusion of water molecules inside and outside the cells, resulting in reduced free diffusion of total water molecules at the ischemic site, swelling of white matter fiber bundles at the infarct site, limited movement of water molecules, increased diffusion anisotropy, and increased FA value [ 10 ]. Hong et al found that the angiogenesis of malignant brain tumors is more than that of benign tumors, and the density of tumor cells in the parenchyma is also relatively large.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gattringer et al analyzed the effect of magnetic resonance diffusion imaging in central system diseases [ 9 ]. Li et al found that in acute cerebral infarction, a large number of water molecules enter the cells, resulting in intracellular edema and reduced diffusion of water molecules inside and outside the cells, resulting in reduced free diffusion of total water molecules at the ischemic site, swelling of white matter fiber bundles at the infarct site, limited movement of water molecules, increased diffusion anisotropy, and increased FA value [ 10 ]. Hong et al found that the angiogenesis of malignant brain tumors is more than that of benign tumors, and the density of tumor cells in the parenchyma is also relatively large.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, we outlined and extracted image information based on primary tumours rather than lymph nodes [ 29 31 ]to promote to the clinical simplicity and operability. On the one hand, it is difficult to evaluate every lymph node on cross-sectional images because of the limitations of imaging range and lymph node size [ 12 ]. On the other hand, LNM is fundamentally driven by the primary tumour, and image-based DL analysis of primary tumours may reveal characteristics that relate to the risk of LNM [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning is also worthy of further research. Li et al 19 identified and detected LN status by using a pretrained deep learning model (Inception‐v3), with an AUC and accuracy of 0.994% and 95.7%, respectively, which showed better performance than radiologists. Lateral lymph node metastasis influences the surgeon's choice of surgical procedure.…”
Section: Clinical Applications Of Ai In Rc Based On Mrimentioning
confidence: 99%